Korespondencja (1950)
Kopie brul. listów do następujących, S-Sr.:
Mf 11054
Keywords: Zakopane; Warszawa Ministerstwo Kultury i Sztuki 20 w; Tarnów; Państwowy Teatr Ziemi Krakowskiej i Ludwika Solskiego 20 w